Efficacy and safety of antidiabetics agents in gestational diabetes mellitus (GDM): a literature review - Rommy; Aldia Dwi Karinaningrum; Berliana Luthfiananda; Laduna Aniq; Lydia Sherly Evelina; Rifani Fauzi (Indonesian Journal of Pharmacology and Therapy, 2022)
One of the most common metabolic diseases during pregnancy period is gestational diabetes mellitus (GDM). It is associated with several perinatal complications, especially in those who have risk factors such as obesity, polycystic ovary syndrome, and a family history of type 2 diabetes mellitus (DM). Some research has shown that physical exercise and medical nutrition treatment can give beneficial effects to control glycemic and body weight for GDM affected women. Furthermore, pharmacological agents such as insulin and a specific oral antidiabetic can be prescribed safely during pregnancy to decrease maternal glucose blood. Therapy of GDM is needed to control blood for the wellness of the patient during and after the pregnancy. The main treatment therapy for GDM is lifestyle modification, which includes medical nutritional therapy and daily physical exercise. In the special case of disorder glucose level, drug therapy will be given to the patient. Insulin is the chosen drug because it is safe and does not cross the placenta. It is the gold standard pharmacological agent for GDM treatment. However, it still has some disadvantages such as the difficulties of how to use it, how many doses must be given, and the price that tends to be expensive. Consequently, the alternative drug may have to substitute it. Insulin can be substituted by metformin and glyburide (glibenclamide) in the form of oral antidiabetic. They are equal in terms of efficacy and safety compare to insulin as a treatment for GDM. Besides, they are also cheaper, and easy to use.